Cognitive impairments associated with CFS and POTS - Jason, Leonard A.; Shanks, Lindzi L.; Evans, Meredyth; Brown, Abigail (Frontiers in Physiology, 2013)
Chronic fatigue syndrome (CFS) is characterized by fatigue, sleep dysfunction, and cognitive deficits (Fukuda et al., 1994). Research surrounding cognitive functioning among patients with CFS has found difficulty with memory, attention, and information processing. A similar disorder, postural tachycardia syndrome (POTS), is characterized by increased heart rate, fatigue, and mental cloudiness (Raj et al., 2009). Potential implications of cognitive deficits for patients with CFS and/or POTS are discussed, including difficulties with school and/or employment. A few biological theories (i.e., kindling, impairments in the central nervous system, and difficulty with blood flow) have emerged as potential explanations for the cognitive deficits reported in both CFS and POTS Future research should continue to examine possible explanations for cognitive impairments in CFS and POTS, and ultimately use this information to try and reduce cognitive impairments for these patients.